The effect of humic substances on the functional state of internal organs and antioxidant status in dogs with myxomatous mitral valve disease - V. V. Rymskyi; V. S. Nedzvetsky (Ukrainian Journal of Veterinary and Agricultural Sciences)
Oxidative stress and reactive oxygen species imbalance have a multifactorial harmful effect on the cardiovascular system, which leads to dysregulation of calcium channels, formation of fibrosis, apoptosis, hypertrophy of cardiomyocytes, as well as inflammatory processes. The role of impaired redox reactions in the body of animals suffering from myxomatous mitral valve disease (MMVD) has not been sufficiently studied. That is why the goal of our research was to study the impact of heart disease on the formation of oxidative stress, as well as to analyse the use of a remedy based on humic substances on the formation of antioxidant protection and the functional state of the organs of the abdominal cavity. The results of our study showed that humic substances do not have a negative effect on kidney function and protein metabolism. Serum levels of electrolytes, namely sodium, potassium, and chlorine, did not show any changes in either group during the study period. The functional state of the hepatobiliary system during the use of humic substances also did not change and did not exceed the threshold values. Thus, the level of ALT on the 21st day of the study in the group of standard therapy (ST) and the group of animals that received humic compounds along with standard therapy (STH) increased by 12.8 % and 20.4 %, respectively. The level of AST in the ST group decreased by 7.9 % and in the STH group it increased by 3.8 %. Indicators of antioxidant protection activity significantly changed by the 21st day of the study in the STH group, so the level of SOD decreased by 25 %, and the level of catalase, on the contrary, increased by 28.5 %. In general, the obtained results indicate the absence of toxic effects of humic substances on the functional state of the hepatobiliary system and kidneys, and demonstrate improvement of the antioxidant protection of the body of dogs with MMVD stage C according to the classification of the American College of Veterinary Internal Medicine.